The Effect Of Particle Size And Type Of Soil Towards The Resistivity For Groundwater Interpretation - Khairul Anuar, Mira Madihah Binti; Madun, Aziman (Recent Trends in Civil Engineering and Built Environment, 2022)
Electrical resistivity tomography (ERT) is a non-destructive method of groundwater surveying where the current is being injected into the ground and the value of the subsurface resistivity are determined. One of the major problems in groundwater surveying is the interpretation of the groundwater aquifer under saturated condition. The overlapping resistivity value under a saturated condition is a major concern in groundwater aquifer interpretation. The interpretation data in the previous research was lack in resistivity for soil data. Hence, by using soil box and soil cylinder connected with ABEM Terrameter LS2, resistivity value 7 sample of soils which were well graded gravel, poorly graded gravel, poorly graded gravel-sand-silt/clay mixture, well graded sands gravelly sands, poorly graded sands gravelly sands, poorly graded sand-silt/clay mixture and silty clays can be recorded in this study. A data of resistivity values of for the soils were established by conducting laboratory tests in saturated conditions. The main objective of this study was to identify the effect of particle size towards the resistivity value. Besides that, the second objective of this study was to establish the effect of type of soil towards the resistivity value and lastly to analyze the resistivity value for particle size/type of soil under different resistivity value of water which were distilled water (5700 Ωm), tap water (500 Ωm) and groundwater (52 Ωm). The highest resistivity value in this study was well graded gravel with 288.6 Ωm and the lowest resistivity value was the silty clay with 6.2 Ωm that tested with distilled water. The presence of silt/clay in the soil samples reduced the resistivity value amount as shown from both sample of poorly graded gravel-sand-silt/clay mixture that tested with distilled water and groundwater as each sample had a low resistivity value of 63.50 Ωm and 97.67 Ωm. This study helps in clarifying the effect of particle size for resistivity value as the larger particle size increases the resistivity value.